Distribution of public investment in physical therapy and supplementary health coverage in Brazil: historical series from 2010 to 2015 (Fisioterapia e Pesquisa, 2017)
This study aims to describe the profile of public investments in physical therapy and to verify the correlation between these investments and the health insurance coverage rate in major Brazilian regions and Federation units, between 2010 and 2015. Data concerning the approved public investments by region and Federation units according to physical therapy attendance were obtained in the Outpatient Information System of the Unified Health System, in the website of the Department of Informatics of the Unified Health System (Datasus). The information corresponding to the health insurance coverage rate was obtained in the Supplementary Health Information sector, available on the National Supplementary Health Agency website. Data were analyzed and the Spearman correlation test was held with a significance level of 5.00% to show a correlation between investment distribution and health insurance coverage rate. The mean per capita application in Brazil, in Brazilian Reais, of financial resources in physical therapy attendances, over the five years analyzed, was R$ 117.16 (±3.52). Among the regions, and for the same period, the South region presented the highest mean per capita (R$ 129.95±5.30), followed in descending order by the Southeast (R$ 124.22±3.69), Northeast (R$ 118.98±7.53), North (R$ 89.43±3.01), and Midwest (R$ 77.09±6.54) regions. The mean coverage by private health insurance varied from 6.20% (Acre) to 43.35% (São Paulo). Apparently, no correlation exists between private health insurance coverage and public investment in physical therapy services.